An interaction between exercise order and rest interval during lower-body resistance exercise - Arazi, H.; Mirzaei, B.; Sangdevini, M.; Abadi, M. R. H. (Baltic Journal of Health and Physical Activity, 2012)
Background: The purpose of the present study was to compare the influence of two- and five-minute rest intervals on the number of repetitions per set and total repetitions per exercise for a lower-body workout performed in 2 different sequences.